2011
DOI: 10.1186/1556-276x-6-380
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of ultra-long platinum nanolawns on a semiconductor photocatalyst

Abstract: A template- and surfactant-free process, thermally assisted photoreduction, is developed to prepare vertically grown ultra-long Pt nanowires (NWs) (about 30-40 nm in diameter, 5-6 μm in length, and up to 80 NWs/100 μm2 in the wire density) on TiO2 coated substrates, including Si wafers and carbon fibers, with the assistance of the photocatalytic ability and semiconductor characteristics of TiO2. A remarkable aspect ratio of up to 200 can be achieved. TEM analytical results suggest that the Pt NWs are single-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The inserted electron diffraction pattern constructed by the fast Fourier transform also verifies the preferred growth direction to be <111>. Similar results have been reported in our previous work [ 28 ].…”
Section: Resultssupporting
confidence: 89%
“…The inserted electron diffraction pattern constructed by the fast Fourier transform also verifies the preferred growth direction to be <111>. Similar results have been reported in our previous work [ 28 ].…”
Section: Resultssupporting
confidence: 89%
“…The results revealed that the shorter electrode is more active due to its high mass transfer rate, besides, the tip end position was more active than the sidewall position. In the research of Shen and coworkers [61], Na2Pt(OH)6 as the precursor was dropped onto TiO2 coated substrates, and then the samples were isothermally heated at 300 °C for 3 h in air by an infrared furnace. The Pt NWs, with an average diameter of 34 nm and the remarkable length of 6 μm (a superb aspect ratio of up to 200), were prepared using the excellent photocatalytic feature of TiO2.…”
Section: Other Methodsmentioning
confidence: 99%
“…Instead of commonly used precursor, H 2 PtCl 6 , Na 2 Pt(OH) 6 was adapted in this study because Pt ions can be reduced more easily mainly due to the smaller electronegativity of the OH group (3.02) [18,19] compared with Cl (3.16). The solution was then isothermally heated to reflux at 100°C, 170°C, and 200°C.…”
Section: Methodsmentioning
confidence: 99%
“…Ag NWs thus prepared were removed from the TiO 2 substrate by ultrasonic oscillation and then immersed in 0.05 M aqueous Na 2 Pt(OH) 6 solution for the exchange of Pt (step 4 in Figure 1 ). Instead of commonly used precursor, H 2 PtCl 6 , Na 2 Pt(OH) 6 was adapted in this study because Pt ions can be reduced more easily mainly due to the smaller electronegativity of the OH group (3.02) [ 18 , 19 ] compared with Cl (3.16). The solution was then isothermally heated to reflux at 100°C, 170°C, and 200°C.…”
Section: Methodsmentioning
confidence: 99%